Model Tests on a Modified 'Wind' Class Icebreaker for the United States Coast Guard. II - Dix, P. J. (1966)
In these tests the craft was run into ice fields of progressively increased thickness until the condition was found in which forward progress was only just possible without resort to charging the ice edge from some distance off. As requested in the contract, the choice of limiting speed at which the icebreaking process could be said to be continuous was taken to be 3.0 knots. The experiment data showed that the maximum thickness of ice which could be broken by the craft when in continuous forward motion would be as follows -- 10,000 S.H.P. - 5.6 ft., 20,000 S.H.P. - 8.4 ft., 30,000 S.H.P. - 10.6 ft., and 40,000 S.H.P. - 12.2 ft. The removal of the forward bossing has obviously improved the performance of the craft when continuously icebreaking. The craft now trimmed more, rode further up onto the ice and in consequence was able to break ice of a greater thickness. Original contains color plates: All DDC reproductions will be in black and white. Original may be seen in DDC Headquarters. See also AD-861 593L.